Media framing of migrant labour in UK fruit and vegetable production: An analysis of reporting in UK farming and mainstream print press. (October 2022) - Broomfield, Catherine; Nye, Caroline; Wells, Rebecca
Abstract: This study explores how UK mainstream and farming print press report the issues arising from the prevalent use of migrant labour in UK horticulture. Domestic fruit and vegetable production is central to achieving transition to a sustainable diet with positive health, environment and social outcomes, including for its 80, 000+ migrant workers. How policymakers understand the issues will determine whether the policy actions they take will address the underlying causes of UK horticulture's dependency on low-paid migrant labour. This study conducts a qualitative content analysis of 92 articles in leading national farming and mainstream press between February 01, 2015–June 26, 2020. Findings show that reporting in both press was significantly slanted toward concerns and interests of farm business groups, correlated with prominent representation of this groups' voice in reporting. This contrasts with minimal presence of the voices of migrant workers and social reform stakeholders. Both press deployed an economic frame in which migrant workers were discussed in purely commercial terms. The prevailing market model of journalism increases the potential for well-resourced groups to dominate media reporting and shape framing. Such stakeholder groups are unhindered – if not aided – by a largely absent neo-liberal state, creating socio-political conditions which militate against policy reforms to bring about a more economically and socially just supply chain. Highlights: Farming interest groups were the most frequently quoted and mentioned actors in all reporting, consistent with the market model of journalism dominant in UK mainstream press which depends on well resourced interest groups to supply content. Although well resourced elite actors, supermarkets are not quoted in reporting and are barely mentioned by farming interest groups despite the dominance of supermarkets in regulating the supply chain and squeezing producers' margins. Farming interest groups tend to frame dependency on migrant labour as an economic rather than a social issue, and focus on policy fixes rather than fundamental reform of food supply chain dynamics. The outbreak of Covid-19 shifted reporting from an economic frame to an emergent 'valued workers of the nation' framing evoking the 'war-time spirit' as industry and government attempted to mobilise UK workers to 'dig for victory'. When mobilisation failed to materialise at the scale required, reporting shifted 'valued workers' framing on to migrant workers despite obvious differences in status and access to entitlements between migrant and home nation workers.